Caveolin-1 Expression Increases upon Maturation in Dendritic Cells and Promotes Their Migration to Lymph Nodes Thereby Favoring the Induction of CD8+ T Cell Responses - Oyarce, Cesar; Cruz-Gomez, Sebastián; Galvez-Cancino, Felipe; Vargas, Pablo; Moreau, Hélène D.; Diaz-Valdivia, Natalia; Diaz, Jorge; Salazar-Onfray, Flavio Andres; Pacheco, Rodrigo; Lennon-Dumenil, Ana Maria; Quest, Andrew F. G.; Lladser, Alvaro (Frontiers in Immunology, 2017)
Dendritic cell (DC) trafficking from peripheral tissues to lymph nodes is a key step required to initiate T cell responses against pathogens as well as tumors. In this context, cellular membrane protrusions and the actin cytoskeleton are essential to guide DC migration towards chemotactic signals. Caveolin-1 is a scaffolding protein that modulates signaling pathways leading to remodeling of the actin cytoskeleton and enhanced migration of cancer cells. However, whether caveolin-1 is relevant for DC function and specifically for DC migration to lymph nodes is unknown. Here we show that caveolin-1 expression is up-regulated in DCs upon LPS- and TNF-α-induced maturation. Caveolin-1 deficiency did not affect differentiation, maturation or the ability of DCs to activate CD8+ T cells in vitro. However, caveolin-1-deficient (CAV1-/-) DCs displayed reduced in vivo trafficking to draining lymph nodes in control and inflammatory conditions. In vitro, CAV1-/- DCs showed reduced directional migration in CCL21 gradients in transwell assays without affecting migration velocity in confined microchannels or three-dimensional collagen matrices. Additionally, CAV1-/- DCs displayed reduced activation of the small GTPase Rac1, a regulator of actin cytoskeletal remodeling, and lower numbers of F-actin-forming protrusions. Furthermore, mice adoptively transferred with peptide-pulsed CAV1-/- DCs showed reduced CD8+ T cell responses and antitumor protection. Our results suggest that caveolin-1 promotes the activation of Rac-1 and the formation of membrane protrusions that favor DC chemotactic trafficking towards lymph nodes where they can initiate cytotoxic T cell responses